Communication Psychology in the Frame of Da'wah: Urgency and Theory - Malik Ibrahim; Halimah; Nurma Dwi Larasati; Kirina Maynastiti Cahyaning Putri (Universitas Muhammdiyah Yogyakarta, 2023)
The role of communication psychology is certainly very important in providing advice and input related to the problems of each individual, including a preacher in delivering his da'wah message to mad'u. When preaching a da'i needs to understand the psychological condition of the object of da'wah (mad'u) as well as himself as a communicator so that the messages conveyed take place effectively in achieving the desired goal. This study aims to understand and analyze the psychology of communication in the frame of da'wah by describing urgency. In addition, it analyzes the theories of communication psychology in da'wah. This research uses library research methods and data collection techniques using documentation. The results showed that the psychology of communication in the process of da'wah is very important, because without the psychology of communication a da'i cannot convey the message of da'wah effectively and maximally. Some of the psychological theories of da'wah communication contained in these findings include persuasion theory, planned action theory, elaboration of likelihood model (ELM), systematic heuristic theory, cognitive response theory, cognitive dissonance theory, and learning theory.